TECTONICS AND METALLOGENY OF THE UCHUR-BUREYA-KHANKAI ORE BELT - Zhirnov A.M.; Lobov A.I. (My University, 2002)
The new Far East transregional ore belt of the meridional strike is considered. It was theoretically and practically justified in the last two decades. The structural base of the ore belt is an elongated (more than 3000 km) Archean lineament between 130° and 133° eastern longitudes. It is 100-150 km wide and consists of three second-order lineaments striking by the 130°, 131°, and 132° meridians. The main metallogenic zones and ore districts of the eastern Aldan-Stanovoi region and Bureya and Tzyamusy-Khankai massifs with the essentially noble metal, iron, and uranium rare metal mineralization are concentrated in this belt. The large polychronous ore districts and deposits are localized at the lineament intersections with latitudinal and diagonal faults pronounced in the relief by morphostructural uplifts.